Evaluando el estado de la biodiversidad: el caso de la avifauna de la Serranía de las Quinchas, Boyacá, Colombia - Stiles Hurd, Frank Galfierd; Bohórquez, Clara Isabel (Caldasia, 2000)
Using sight and auditory records made during extensive observations, supplemented by mist-net captures and tape recordings, we made an inventory of the birds of three sites differing in elevation and degree of human transformation of the landscape, in the Serranía de las Quinchas in the middle Magdalena valley of Colombia. We estimated per cent cover of different habitat types in each site and abundances of birds in each, based upon encounter frequencies, and developed an ecological classification of the birds that emphasized their degrees of association with primary, disturbed or manmade habitats. With 10-1 3 field days per site and a total of 833 birds captured in 1083 net-hours, we recorded a total of 308 species in the studv area. The form of the species accumulation curves and distributions of abundances indicated that the samples from the three sites were comparable. The numbers and abundances of species in different ecological categories varied in accord with the representation of the different habitat types between sites; the two sites with the largest extensions of primary forest had greater species richness. The majority of forest-restricted species occurred at a single site; on average, the most generalized species with respect to tree cover occured in two or more sites; and species of open habitats occurred in one site (elevation specialists) or all three. Most species were breeding in April, also the best month for auditory records. The suboscine passerines of the suborder Furnarii (antbirds, ovenbirds and allies) include the largest single group of forest- restricted species which could serve as an indicator of the state of conservation of forest habitat, provided the appropriate species are chosen - most families include species with diverse habitat requirements. The scarcity or absence of several groups subject to hunting pressure was noteworthy in an otherwise healthy forest avifauna. The known or suspected presence of several endangered species makes the Serranía de las Quinchas worthy of protection, especially given the lack of other conservation areas in the Magdalena valley, an important center of endemism of Colombian birds.